Efectos de la leptina en el inicio de la pubertad en animales machos - Quintero, Juan C.; Ruiz Cortés, Zulma T. (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The leptin is a 16 KDa hormone principally produced by the adipose tissue, codified by the ob gene and composed by 146 amino acids. This hormone carries out its functions at peripheral levels and in the hypothalamic- hypophysis - gonadal axis. In several species the effect of this hormone on reproduction and their concentration and expression changes might be associated with the onset of puberty in different animal species and in human beings. The role of leptin in male reproduction has been studied especially in rats, mice, human beings, and other animal species. Leptin receptor and mRNA expression has been found in Leydig cells, seminiferous tubules, spermatogonies, spermatozoa, among other cells, indicating that leptin could have an important role in testicular function. An inhibitory effect of testosterone on leptin secretion has been found and vice versa, which indicates that leptin can regulate testicular steroidogenesis. Leptin can also act in non differentiated cells of the testis, promoting spermiogenesis. Then, leptin appears to be an important hormone probably involved in vital functions of the male neuroendocrine and reproductive axis.